Beta-glucans in higher fungi and their health effects - Rop, Otakar; Mlcek, Jiri; Jurikova, Tunde (Nutrition reviews, 2009)
Together with chitin, the beta-glucans are components of mycetes' cell walls. A high level of biological efficiency has been found in beta-glucans, especially beta-1,3-D-glucans and beta-1,6-D-glucans isolated from some basidiomycetes. (Biological efficiency refers to the relative ability of beta-glucans to promote a desired response, for example to induce leukocyte activation and to produce inflammatory mediators.) These polysaccharides increase the number of Th1 lymphocytes, which help protect organisms against allergic reactions. A number of beta-glucans, for example pleuran from Oyster (Pleurotus spp.) mushrooms or lentinan from Shiitake (Lentinus edodes) mushrooms, have shown marked anticarcinogenic activity. In addition to having an immunity-stimulating effect, beta-glucans may participate in physiological processes related to the metabolism of fats in the human body. Their application results in a decrease in the total cholesterol content in blood and may also contribute to reductions in body weight.
Keywords: metabolismus lipidů; Humans; Lipid Metabolism; T-Lymphocytes; Agaricales; beta-glukany; beta-Glucans; Antineoplastic Agents; lidé; zvířata; Lentinan; Neoplasms; protinádorové látky; nádory; buněčná stěna; T-lymfocyty; Animals; Basidiomycota; Cell Wall; lentinan